Genome-wide data from two early Neolithic East Asian individuals dating to 7700 years ago - Bradley, Daniel; Siska, Veronica; Jones, Eppie Ruth; Jeon, Sungwon; Bhak, Youngjune; Kim, Hak-Min; Cho, Yun Sung; Kim, Hyunho; Lee, Kyusang; Veselovskaya, Elizaveta; Balueva, Tatiana; Gallego-Llorente, Marcos; et al. (My University, 2017)
Ancient genomes have revolutionized our understanding of Holocene prehistory and, particularly, the Neolithic transition in western Eurasia. In contrast, East Asia has so far received little attention, despite representing a core region at which the Neolithic transition took place indep endently ~3 millennia after its onset in the Near East. We report genome-wide data from two hunter-gatherers from Devil ’ s Gate, an early Neolithic cave site (dated to ~7.7 thousand years ago) located in East Asia, on the border between Russia and Korea. Both of these individ- uals are genetically most similar to geographically clos e modern populations from the Amur Basin, all speaking Tungusic languages, and, in particular, to the Ulchi. The s imilarity to nearby modern populations and the low levels of additional genetic material in the Ulc hi imply a high level of genetic continui ty in this region during the Holocene, a pattern that markedly contrast s with that reported for Europe
Keywords: Holocene prehistory; Ancient genetics; East Asia; Neolithic; Russian Far East; Human population genetics